(untitled) (Tanzania Medical Journal, 2021)
Background Intestinal helminth infection is associated with altered immune responses and deranged micronutrient status in infected children. There is no information on the status of serum cytokine levels and micronutrient status in Ascaris lumbricoides infected Nigerian school children at pre- and post- albendazole anti-helminthic treatment. Aim To provide data on serum levels of cytokines and micronutrients in Ascaris lumbricoides infected Nigerian children at pre- and post- albendazole anti-helminthic treatment. Method This case-control prospective study assessed serum levels of micronutrients (zinc, iron, selenium, vitamin A, vitamin C), transferrin and cytokines (TNF–?, IFN–?, IL-6, IL-8, IL-4 and IL-10) in 46 Ascaris lumbricoides infected and 40 uninfected Nigerian school children before and after anthelminthic treatment using Atomic Absorption Spectrophotometry, high performance liquid chromatography (HPLC) and Enzyme Linked Immunosorbent Assay (ELISA) as appropriate. Data were analysed using Mann-Whitney U test, Wilcoxon Signed Ranks Test and Kruskal Wallis Test, with levels of significance set at ?0.05. Results More males than females were infected with helminthes and most helminth infected schoolchildren were within 5-9yrs of age. Ascaris lumbricoides has the highest prevalence. Most (77%) children were infected with Ascaris lumbricoides and 2% of the children had co-infection of Ascaris lumbricoides with hookworms and Trichuris trichiuria. Pre-albendazole anti-helminth treatment, serum zinc and vitamin A levels were significantly lower (p=0.044 and p=0.002 respectively) while transferrin, selenium, IL-8, IL-6, IFN–? and IL-4 levels were significantly higher (p=0.001, p=0.032, p=0.014, p=0.001, p=0.014 and p=0.010 respectively) in Ascaris lumbricoides-infected group compared with controls. Serum vitamin A levels were significantly higher at one month (p=0.001) and two months (p=0.001) post-albendazole treatment while IL-8 (p=0.031) was significantly lower at one month compared with pre-treatment values. Conclusion Inflammation, zinc and vitamin A deficiencies associated with A. lumbricoides infection in Nigerian children were reversed from one month of albendazole. Recommendation Periodic anthelminthic drug treatment coupled with taking diet containing zinc and vitamin A by school children is recommended. Keywords: Albendazole, Ascaris lumbricoides, Cytokines, Zinc, Vitamin A, School children.